Inflammatory pseudotumour of the urachus: case report and literature review - Wu, Yunfeng; Li, Jiajia; Jie Yan; Yao Wang; Guangxian Miao; Wu, Zuohui (Journal of the Pakistan Medical Association, 2023)
A 52 year old woman presented to the emergency department of Affiliated Hospital of Zunyi Medical University in May 2022, complaining of a palpable lower abdominal mass since two days. She denied haematuria, umbilical drainage, or any other urinary symptoms. Previous physical health. Patient was diagnosed with urachal inflammatory pseudotumour. Inflammatory pseudotumourous masses of the urachal canal are rare chronic inflammatory disorders with only a few case reports. Ultrasonography is the preferred method for diagnosing urachal lesions. Contrast-enhanced ultrasonography (CEUS) allows real-time visualization of the microvascular blood flow within the solid lesion, reducing the probability of misdiagnosis of the disease. We have reported a case of urachal inflammatory pseudotumour and analyzed its ultrasonographic findings from two-dimensional conventional ultrasonography and CEUS to provide support for the diagnosis of urachal inflammatory pseudotumour in the clinic and to assist clinical selection of effective treatment modalities. Keywords: Urachus. Inflammatory pseudotumor. Ultrasonography. CEUS.